Teaching Speaking Skills by Overcoming Classroom Problems for Teachers and Lectures - Nining Wulandari (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2016)
This article is written for teachers with large classes of students who have encountered some of the following or similar problems during speaking activities in their classroom. Speaking is fundamental to human communication. Dealing with the arguments against teaching speaking skills. Student's won't talk or say anything. When students work in pairs or groups they just end up chatting in their own language. When all the students speak together it gets too noisy and out of hand and I lose control of the classroom. Many students equate being able to speak a language as knowing the language and therefore view learning the language as learning how to speak the language, or as Nunan (1991) wrote, "success is measured in terms of the ability to carry out a conversation in the (target) language." Therefore, if students do not learn how to speak or do not get any opportunity to speak in the language classroom they may soon get de-motivated and lose interest in learning. On the other hand, if the right activities are taught in the right way, speaking in class can be a lot of fun, raising general learner motivation and making the English language classroom a fun and dynamic place to be. Keyword: Speaking skill,Overcome,classroom problem